2013
DOI: 10.1186/1471-2369-14-167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ferric carboxymaltose on serum phosphate and C-terminal FGF23 levels in non-dialysis chronic kidney disease patients: post-hoc analysis of a prospective study

Abstract: BackgroundSome parenteral iron therapies have been found to be associated with hypophosphatemia. The mechanism of the decrease in serum phosphate is unknown. The aim of this study is to examine the effect of IV ferric carboxymaltose(FCM) on phosphate metabolism and FGF23 levels in patients with chronic kidney disease(CKD).MethodsThis is a post-hoc analysis of a prospective study carried out in 47 non-dialysis CKD patients with iron-deficiency anaemia who received a single 1000 mg injection of FCM. Markers of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 44 publications
3
59
2
3
Order By: Relevance
“…However, the study of Prats et al was longer and the changes in serum phosphate persisted for 3 months [15]. That study showed, among others, that a single high dose of IV iron (1000 mg) may lead to significant changes of FGF23 and serum phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study of Prats et al was longer and the changes in serum phosphate persisted for 3 months [15]. That study showed, among others, that a single high dose of IV iron (1000 mg) may lead to significant changes of FGF23 and serum phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…In another study the use of ferric carboxymaltose, in non-dialysis patients, Prats et al showed a reduction of serum phosphate levels that persisted for up to 3 months after iron infusion and it was associated with a decrease of serum FGF23 but there were no changes of other bone metabolism parameters [15]. These results are consistent with ours at least in the short-term, since we did not observe any significant changes of plasma BAP, PTH or serum calcium concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After oral or intravenous iron, various FGF23 responses were registered depending on the iron type and the population [21,22]. The decrease of phosphate after iron in the HD population is probably the result of the PTH decrease, and contrary to the healthy population, no iFGF23 increase was detected [23][24][25]. Whatever the iron form used and the population considered, iron administration decreases cFGF23 by decreasing the transcription of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…La duració n de la HF en el presente estudio presenta mayor incertidumbre debido a la falta de datos en algunos pacientes pero, asumiendo la ausencia de HF en los pacientes en los que no se determinó el fosfato sé rico, la incidencia real de HF se situaría al menos en el 20% para el P22-35 y en el 6% para el P60-180. Prats et al 7 han encontrado que los pacientes que desarrollan HF mantienen concentraciones por debajo de la basal a las 12 sem de la infusió n de HCMiv.…”
Section: Discusió Nunclassified